CLINICAL FACTORS AND ANTICOAGULATION LEVEL THAT DETERMINE THE SUDDEN LOSS OF KIDNEY FUNCTION IN PATIENTS LONG-TAKING WARFARIN (A 5-YEAR PROSPECTIVE, OBSERVATIONAL STUDY) - E. S. Kropacheva; O. A. Zemlyanskaya; A. В. Dobrovolsky; Е. P. Panchenko («REMEDIUM GROUP» Ltd., 2018)
Assessment of kidney function is mandatory in all cardiac patients, and patients with atrial fibrillation represent a category of patients with high thrombotic risk, which increases the risk of decreased kidney function during follow-up. Controversial issues of warfarin-associated nephropathy are important today. A prospective 5-year follow-up of 172 patients receiving warfarin therapy showed that 26.7% had the sudden loss of renal function (SLRF) (defined as an annual decline in glomerular filtration rate (GFR) ≥ 3 ml/min/1.73 cm2). Based on the results of the ROC analysis, it was determined that the maximum INR > 3.97 was associated with the SLRF (the area under the curve was 0.649, the sensitivity 56.5%, the specificity 74.6%, p = 0.003), and the maximum INR> 6.0 increased the specificity of the analysis to 96%. The study showed that for patients who had a maximum INR value ≥ 3.97, the mean delta of changes in GFR was negative, and the largest negative dynamics was characteristic for patients with a maximum INR ≥ 6.0. The estimated odd ratio of SLRF confirms the high prognostic significance of the maximum INR value. The maximum INR 3.97-5.9 increased the risk of SLRF by 3.07 times (95% CI 1.5241-6.2017, p = 0.0017), as well as the INR ≥ 6.0 (OR 3.05, 95% CI 1.0073-9.2433, p = 0.0485). The multifactorial discriminant analysis showed that the SLRF predictors against the background of 5-year warfarin therapy included the maximum INR ≥ 3.97 (F = 10.45, p = 0.0014), IHD (F = 8.7, p = 0.0036), diabetic nephropathy (F = 5.29, p = 0.0226) and the CHA2DS2-VASc score ≥ 4 (F = 5.05, p = 0.0258).